PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF BERBASIS AKHLAK DALAM KURIKULUM 2013 - Neny Suharni Sofyan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is a research on the development of moral-based cooperative learning models in the application of the 2013 curriculum in elementary schools. The purpose of this study was to determine the level of validity and feasibility of the developed model. This research is a research and development (R&D and R&D) at SDN Dumai City. This development is carried out on the moral-based cooperative learning model in the application of the 2013 Curriculum at SDN Dumai City. The results showed the Graphic Design indicator got a validation score of 79.00 in the good category, the language effect received a validation score of 78.00 in the good category, and the content content effect received a validation value of 83.00 in the good category. While the results of the implementation, the results showed in SDN 002 Big Chart the results of the first trial got a score of 78 with a percentage of 46.33%, after the second trial the results of the study increased to 101 with a percentage of 59.83%, and again increased in the third trial to 134 with a percentage of 79.33%. While the implementation in SDN 004 Bagan the first tryout got a score of 61 with a percentage of 48.4% and increased in the second trial to 80 with a percentage of 63.4%, while in the third trial again increased to 91 with a percentage of 72%. From the results of the study it can be concluded that the development of a moral-based cooperative learning model in the implementation of 2013 curriculum produced a valid and reliable moral-based cooperative manual (KBA) and was able to increase student interaction and learning outcomes.